The Decline of the British Motor Industry (Routledge Revivals) : the Effects of Government Policy, 1945-79. - Dunnett, Peter (Taylor & Francis, 2011)
First published in 1980, this book considers the British motor industry over the period between 1945 and 1979, analysing the€ways€in which the industry suffered a considerable decline in the post-war era, when compared to motor industries of other countries or to most other British industries.